Analisis Psikologi Sastra dalam Naskah Drama dan Relevansinya dengan Pembelajaran Bahasa Indonesia - Radita Rahmawati; Ghina Ayu Salsabila; Rizka Maulidania; Retna Ayu Ratu Gumilang; Adita Widara Putra (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to analyze the psychology of literature contained in the drama Penambang Emas by Budi Riswandi. This research was conducted using qualitative methods and analysis techniques for psychology aspects of literature to analyze the drama script. The data used is the drama script Penambang Emas by Budi Riswandi. Data were analyzed using a literary psychology approach. By using a psychology approach, readers can understand the inner conflict contained in literary works. The results of the research show that the drama script has 12 data, namely id totaling 4 data, ego totaling 4 data, and super ego totaling 4 data.